Quality management for buildings : improving building performance through technical monitoring and commissioning - Plesser, Stefan; Teisen, Ole; Ryan, Cormac (REHVA, 2019)
New buildings and deep retrofits often use innovative technologies for heating, cooling and air conditioning (HVAC). These sophisticated technical concepts and the associated building automation and control systems have added complexity and are a huge challenge to designers, engineers, construction companies and facilities managers. Consequently, the performance gap appeared: buildings do not work as intended and miss their initial performance targets in operation. This is doubly costly: first, design and construction cause additional cost and then, later, operation and maintenance cost are also higher than expected. Solutions to this problem can be found in other industries: quality management. In engineering, "quality" describes the degree to which a set of inherent characteristics of an object fulfils requirements. In short: a building owner should get what he pays for! Consequently, "quality management" is a process of supporting the fulfilment of requirements. Over the last years, two solutions have evolved as reliable quality management services for buildings and are becoming increasingly popular: Technical Monitoring and Commissioning.
Keywords: Buildings -- Performance.; Buildings -- Energy conservation.; elektronické knihy; electronic books